Some Socio-Economic Characteristics of the Upper Luni Basin in Rajasthan Desert - Bharara, L P; Khan, W; Mathur, Y N (Annals of Arid Zone, 2016)
Socio-economic structure in the Upper Luni Basin showed predominance of agricultural caste groups of Rajput, Seervi, Jat, lali, Bishnoi and Rawat. Population increased by 24% during 1961-71 with 71 persons/sq. km in 1971. Traditional rural joint households had disintegrated into nuclear households. Literacy rate was very low. Cultivation followed by agricultural labour and animal husbandry followed by casual labour were the main and the subsidiary occupations of the population. Over 28% of the total area, though cultivable, was not cultivated. On an average, a household owned 1.05 ha of irrigated and 2.51 ha unirrigated land. Subsistence crops had low yields. Livestock composition revealed predominance (62%) of sheep and goat population. A household, on an average, owned 15 heads of livestock. Traditional livestock rearing .caste group,as compared to other groups, constituted highest mean number (87) of livestock per household. Permanent pastures and other grazing lands were overstocked.